2018
DOI: 10.4103/jisp.jisp_88_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of placental membrane and Healiguide™ in treatment of gingival recession using guided tissue regeneration

Abstract: Background:Guided tissue regeneration-based root coverage has emerged as a promising treatment modality in the treatment of gingival recession. A variety of nonresorbable and bioresorbable membranes have been successfully used. Among resorbable membranes, collagen has been extensively studied. Recently, a third generation barrier membrane derived from placenta has been introduced for periodontal regeneration.Aim:The objective of the present study is to clinically compare the efficacy of placental membrane (Amn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In GBR procedures, gingival tissue enhancement and adequate space maintenance are parameters fundamental for periodontal repair [ 29 , 30 ] Therefore, the membrane thickness should range from 0.2 to 0.5 mm [ 30 ] to provide adequate thickness [ 31 ] for tissue enhancement and space maintenance required for periodontal repair process [ 29 ]. Specifically, membranes 0.2 mm thick facilitate soft tissue manipulation and 0.4 mm is the material of choice among early-generation membranes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In GBR procedures, gingival tissue enhancement and adequate space maintenance are parameters fundamental for periodontal repair [ 29 , 30 ] Therefore, the membrane thickness should range from 0.2 to 0.5 mm [ 30 ] to provide adequate thickness [ 31 ] for tissue enhancement and space maintenance required for periodontal repair process [ 29 ]. Specifically, membranes 0.2 mm thick facilitate soft tissue manipulation and 0.4 mm is the material of choice among early-generation membranes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Ngoc Nguyen et al, in an in vitro study, assessed how the membrane derived from bovine pericardium induced and stimulated attachment, migration, and proliferation of human gingival fibroblasts [ 34 ]. The authors demonstrated how the extracellular matrix of the bovine pericardium membrane can provide adequate support, acting as a cell scaffold [ 31 , 33 ]. As bovine pericardium membranes showed significant biocompatibility with human fibroblasts, by stimulating their migration patterns they may be successfully applied as a guided biomembrane in periodontal reconstruction and regeneration, as suggested by several recent studies on this topic [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This property makes it unique and different from other native collagen membrane and is known to facilitate fibrogenesis over osteoconduction. The porosity is less than the penetrable size of epithelial cell during the initial healing period [ 26 ]. Jim-Charm Kim [ 27 ] expressed that the position of collagen membrane after extraction of impacted third molar diminished the complications post-operatively at the early stage and improved the initial healing of gingival soft tissues and periodontal defects.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo biodegradation of both membranes takes place 6–8 weeks postoperatively (Schliephake et al 1994,. Mahajan et al 2018…”
Section: Discussionmentioning
confidence: 99%